An Instrument to Assess the Digital Competence of Nurse Educators - Pajari, Juha (Lippincott, 2025)
Background: The Educators and Educator Candidates' Competence in Digital Pedagogy instrument needed to be tested before using it in nursing education.
Purpose: This study describes the further testing of this instrument to measure nurse educators' digital competence.
Methods: The study is reported according to the 7 steps of the MEASURE Approach. Psychometric testing was conducted with a sample of 111 Finnish nurse educators from 9 universities of applied sciences. The study was conducted during the years 2020 and 2023.
Results: The exploratory factor analysis results explained 56% of the variance with 3 factors, including 20 items. The factors were labeled to describe the nurse educators' digital competence: implementing appropriate independent and community learning, acting safely and responsibly, and guiding learning based on the evidence. Cronbach α and McDonald ω coefficients showed good reliability.
Conclusions: The instrument can be used to assess digital competence and identify the development needs to facilitate educators' continuous professional development.